Clinical, psychopathological and neurobiological aspects of affective disorders in children and adolescents with epilepsy - Yu. A. Yakovleva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In order to study the clinical and psychopathological characteristics of affective disorders in childhood and adolescence and their relationship to neurophysiological and neuroimaging studies, clinical and psychopathological (using scales of comprehensive assessment of mental state and the Kovach M child depression questionnaire) and instrumental methods (MRI, VEM) examined 134 children and adolescents aged 6 to 18 years, diagnosed with epilepsy. Differences in the frequency of affective symptoms according to the SWAPS data were revealed, depending on the gender of patients and the form of epilepsy, as well as neurophysiological and neuromorphological changes that increase the likelihood of developing comorbid epilepsy affective disorders in childhood and adolescence.